THE ROLE OF RISK MONITORING COMMITTEE IN ENHANCING CORPORATE RISK DISCLOSURE - Multazam, Ahmad; Kurniawati, Estetika Mutiaranisa; Hasim (Faculty of Economics and Business University of Mataram, 2025)
Banking companies face challenges in the transparency of financial risk disclosures, which affects investor confidence and the stability of the banking sector. Effective governance mechanisms are required to enhance accountability and risk mitigation. This research examines and provides empirical evidence on risk monitoring committee characteristics and risk disclosure. The sample is selected through purposive sampling on the banking sector detailed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, yielding 205 observations from 44 companies. The research utilizes secondary data sourced from social media platforms, annual reports, and corporate websites. The data analysis employs multiple linear regression. This research found that gender diversity and the frequency of committee meetings positively influence risk disclosure. Meanwhile, the independent committee and the committee qualifications do not significantly affect risk disclosure. These findings provide a basis for improving corporate governance in Indonesian banks especially risk monitoring committees.